Effect of bedding angle on tunnel slate failure behavior under indirect tension. Issue 1 (1st January 2020) - Wang, Han; Ren, Fuqiang; Chang, Yuan
Abstract: In order to provide guidance for Muzhailin tunnel design and construction, in this study, five groups of slate specimens with different bedding angles ( β, angle between bedding plane and vertical axis) were taken from site to conduct Brazilian splitting tests. The tensile strength, applied energy, failure behaviour, and acoustic emission (AE) characteristics were analyzed, and the failure mechanism was elucidated. The results show that average tensile strength of specimen with β equal to 90° is ∼1.38 times of that of β equal to 0°. Additionally, the applied energy exhibits nonlinear monotonic increasing relationship with bedding angle. Moreover, if β > 45°, the surface crack is noncentral. After the tensile failure, the relative roughness of failure fracture linearly increases with the increase in bedding angle. Furthermore, with increase in β from 0° to 90°, the AE signals occurred around peak loading changed from low amplitude and high frequency to high amplitude and low frequency, i.e. the scale of microcracks increases gradually. When β = 0° and 90°, the tensile failures occurred along the bedding plane and at the slate substrate, respectively. Moreover, when β = 30°, 45°, and 60°, the specimen performed as the shear and tensile composite failure.